2002
DOI: 10.1074/jbc.m204738200
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Domain Anchors Human Topoisomerase I at Fibrillar Centers of Nucleoli and Nucleolar Organizer Regions of Mitotic Chromosomes

Abstract: DNA topoisomerase I releases torsion stress created by DNA transcription. In principle, this activity is required in the nucleoplasm for mRNA synthesis and in the nucleoli for rRNA synthesis. Yet, topoisomerase I is mostly a nucleolar protein. Current belief holds that this preference is triggered by the N-terminal domain of the enzyme, which constitutes a nucleolar import signal. Contradicting this view, we show here that nucleolar accumulation of various fragments of topoisomerase I is correlated with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…To fuse GFP to the C terminus of the N-terminal domain of topo I as described previously (16), the N-terminal topo I fragment (TI ) was inserted into the vector pMC-EGFPP (17) by linker-PCR, giving rise to the construct TI -GFP. All new constructs were checked by DNA sequencing and stably expressed in the human embryonal kidney cell line HEK 293 (German Collection of Microorganisms and Cell Culture, Braunschweig, Germany) as described previously (5,12,15). Like in these previous studies, we have ascertained that all constructs are not overexpressed in relation to endogenous topo I, that the chimeric genes are not rearranged, and that green fluorescence of the cells could be unambiguously assigned to constitutive expression of the intended proteins.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…To fuse GFP to the C terminus of the N-terminal domain of topo I as described previously (16), the N-terminal topo I fragment (TI ) was inserted into the vector pMC-EGFPP (17) by linker-PCR, giving rise to the construct TI -GFP. All new constructs were checked by DNA sequencing and stably expressed in the human embryonal kidney cell line HEK 293 (German Collection of Microorganisms and Cell Culture, Braunschweig, Germany) as described previously (5,12,15). Like in these previous studies, we have ascertained that all constructs are not overexpressed in relation to endogenous topo I, that the chimeric genes are not rearranged, and that green fluorescence of the cells could be unambiguously assigned to constitutive expression of the intended proteins.…”
Section: Methodsmentioning
confidence: 93%
“…Constructs and Cell Culture-Construction and characterization of cell lines supporting stable expression of GFP-topo I, GFP-topo I Phe-723 , GFP-topo I 190 -765 , and GFP-topo I has been documented in previous studies (5,12,15). Please note that in one of these studies (5) GFP-topo I has been incorrectly referred to as GFP-topo I 1-210 , leading to the misunderstanding that it has five residues less than it actually does.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Although this Nterminal domain does not contribute to the enzyme's catalytic activity in vitro, it is very important for in vivo activity, as the enzyme must enter the nucleus to exert its function. [9][10][11] Data have indicated that mutations within the N-terminus of top1 result in loss of nuclear localization and subsequent resistance to topoisomerase I inhibitors. 12 Localization of topo I can be determined using immunofluorescence microscopy in patients with hematologic and solid tumors.…”
mentioning
confidence: 99%